Broadcasting the Movement and Branding Political Microcelebrities: Finnish Anti-Immigration Video Practices on YouTube. (27th April 2020) - Laaksonen, Salla-Maaria; Pantti, Mervi; Titley, Gavan
Abstract: This paper examines how the video-sharing platform YouTube was utilized by networks of anti-immigration activists that began emerging in Finland during the so-called refugee crisis in 2015. By combining network analysis with qualitative analysis, we identified three central strategies of video activism: movement building through documentation, discursive controversy generation, and personal branding practices. These strategies are firmly supported by the affordances of YouTube and by the way in which the platform enables the building of varying scales of media presence. Consequently, our findings highlight the increasingly common practice of microcelebrity branding in online political communication. This notion demonstrates the affinities between fragmented and contingently mobilized anti-immigration movements and the personalizing and performance-oriented logics of social media presence, in particular when explored from a post-movement perspective. In the algorithmic environment of YouTube, microcelebrity is a political and a platform-specific genre that occupies the post-movement political space by generating sustainable algorithmic visibility.